2016
DOI: 10.5301/ejo.5000715
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Chamber Migration of Dexamethasone Intravitreal Implant (Ozurdex®) through Basal Iridectomy (Ando) in a Pseudophakic Patient

Abstract: Pseudophakic patients, with a history of vitrectomy, even those with a basal iridectomy (Ando), are at high risk for migration of the Ozurdex® into the anterior chamber and development of corneal edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…In the presented case, the patient had an intact posterior capsule. As discussed by Stepanov et al [4], an iris defect that is situated in the inferior iris (as in our case) is more susceptible to be a route of passage for an implant, as it usually sinks to the bottom of the vitreous cavity.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In the presented case, the patient had an intact posterior capsule. As discussed by Stepanov et al [4], an iris defect that is situated in the inferior iris (as in our case) is more susceptible to be a route of passage for an implant, as it usually sinks to the bottom of the vitreous cavity.…”
Section: Discussionmentioning
confidence: 54%
“…First was Stelton et al [5], who described a patient with PCIOL and a disrupted posterior capsule that also had a large peripheral inferior iridectomy. Later, Stepanov et al [4] described a patient that underwent inferior iridectomy due to silicone oil insertion during pars plana vitrectomy for treating retinal detachment, which was later on implanted with iris-claw ACIOL (Artisan). Although it is fairly likely that in both cases the implant migrated through the iris defects, both patients also had the "classic" risk factors (prior pars plana vitrectomy and disrupted lens capsule).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients treated with the 0.7 mg insert (the dose that was eventually approved by the FDA) in the 36-month registration trials, 41.5% required topical IOP lowering medications, but only 0.3% required incisional glaucoma surgery. 50 The dexamethasone delivery system may migrate into the anterior chamber in pseudophakic or aphakic eyes, 51 which requires surgical removal ( Figure 2 ). 52 Less frequently reported complications include endophthalmitis, 53 acute retinal necrosis due to varicella zoster virus, 54 and retinal and vitreous hemorrhage due to retinal impact during injection.…”
Section: Dexamethasonementioning
confidence: 99%
“…Efficacy and safety of this treatment are well documented. Complications of the implant injections such as migration in the anterior chamber throught iridotomy or in case of aphakia have already been described (Stepanov et al 2015 ). Accidental injections into the crystalline lens (Coca-Robinot et al 2014 ; Fasce et al 2014 ) have also been reported.…”
Section: Introductionmentioning
confidence: 98%